THE RISE OF FACEBOOK MARKETPLACE IN INDONESIA: TRENDS, NEGOTIATION DYNAMICS, AND DIGITAL COMMERCE SHIFTS - Lo, Michaela GY; Kulsum, Nieke M; Darmawan, D (Universitas Nasional, 2025)
The rapid expansion of Facebook Marketplace has redefined the landscape of digital commerce in Indonesia, serving as a low-barrier platform that facilitates informal buying and selling activities. In the context of increasing internet penetration and the widespread adoption of online shopping—exacerbated by the COVID-19 pandemic—this platform has become an essential medium for everyday economic transactions. This study explores the dynamics of negotiation and communicative behavior among Indonesian users of Facebook Marketplace, with particular attention to broader shifts in consumer interaction patterns within digital environments. Employing a qualitative, phenomenological methodology, this research focuses on the lived experiences of two experienced users selected through purposive sampling. Data were gathered via in-depth interviews and naturalistic observation, and analyzed through the stages of data reduction, data display, and conclusion drawing, following the analytical framework of Miles and Huberman. The findings indicate that negotiation practices on Facebook Marketplace constitute strategic and performative acts, heavily influenced by users’ digital literacy, impression management strategies, and responsiveness to social cues. Informants engaged in storytelling, employed multiple accounts, utilized emotional appeals, and adopted persuasive linguistic techniques to shape negotiation outcomes. These practices are interpreted through Goffman’s dramaturgical theory, wherein interactions are seen as performances alternating between front-stage and back-stage behavior. Despite the absence of physical presence, users rely on digital semiotics—such as emojis, tone modulation in text, and contextual signaling—to convey intentions and cultivate trust. This research contributes to the understanding of digital negotiation in Southeast Asian social commerce contexts, highlighting the ways in which platforms like Facebook Marketplace foster novel forms of economic participation, digital communication, and self-presentation.